Spiritual skepticism? Heterogeneous science skepticism in the Netherlands - Rutjens, Bastiaan T. (Public Underst Sci, 2020)
Recent work points to the heterogeneous nature of science skepticism. However, most research on science skepticism has been conducted in the United States. The current work addresses the generalizability of the knowledge acquired so far by investigating individuals from a Western European country (The Netherlands). Results indicate that various previously reported findings hold up: Mirroring North American patterns, climate change skepticism is associated with political conservatism (but only modestly), and scientific literacy does not contribute to skepticism, except about genetic modification (Study 1 only) and vaccine skepticism (Study 2 only). Results also reveal a crucial difference: Religiosity does not consistently contribute to science skepticism, except about evolution. Instead, spirituality is found to most consistently predict vaccine skepticism and low general faith in science—which in turn predicts willingness to support science. Concerns about societal impact play an additional role. These findings speak to the generalizability of previous findings, improving our understanding of science skepticism.